1999
DOI: 10.1159/000017404
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Dysplasia, Genetic Abnormalities and Neurocutaneous Syndromes

Abstract: Cortical dysplasia (CD) represents a common neuropathologic substrate of pediatric epilepsy, one frequently encountered in surgical resection specimens from infants and children with intractable seizure disorders, including infantile spasms. Severe CD shows similarities to structural features noted in tubers from individuals with tuberous sclerosis (TSC). The latter disorder, one with neurocutaneous and visceral manifestations, results from mutations in one of two recently cloned genes, TSC1 or TSC2, which enc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 56 publications
1
15
1
Order By: Relevance
“…Cerebral arteriolar media, comprised of smooth muscle cells, exhibits variable hamartin immunoreactivity. No expression is observed in astrocyte or oligodendroglia cell populations, although cortical tubers of TSC patients, which contain cells with both neuronal and astrocytic characteristics, are variably immunoreactive for both hamartin and tuberin (Johnson et al, 1999; Vinters et al, 1999). Within viscera, hamartin is expressed in many tissues, with particularly high expression found in heart, kidney, bronchial epithelia and macrophages, pancreas, and regions of the adrenal cortex.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Cerebral arteriolar media, comprised of smooth muscle cells, exhibits variable hamartin immunoreactivity. No expression is observed in astrocyte or oligodendroglia cell populations, although cortical tubers of TSC patients, which contain cells with both neuronal and astrocytic characteristics, are variably immunoreactive for both hamartin and tuberin (Johnson et al, 1999; Vinters et al, 1999). Within viscera, hamartin is expressed in many tissues, with particularly high expression found in heart, kidney, bronchial epithelia and macrophages, pancreas, and regions of the adrenal cortex.…”
Section: Discussionsupporting
confidence: 92%
“…Western analysis has shown that primary fetal mouse astrocyte cultures express hamartin as well (Gutmann et al, 2000). In humans, hamartin is expressed in neuronal populations as early as gestational age 20 weeks, but is consistently absent from astrocytes, an expression pattern maintained into adulthood (Johnson et al, 1999; Plank et al, 1999; Vinters et al, 1999). A potentially important finding in the brain of a fetus with TSC was sub‐pial radial glia that were either absent or not expressing vimentin and GFAP in regions of cerebral cortex exhibiting cytoarchitectural abnormalities consistent with a cortical tuber, suggesting a possible explanation for abnormal neuronal migration in TSC (Park et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that hamartin and tuberin are expressed in similar neuronal populations within the human CNS as early as 20 weeks of gestation (17,20). This study was performed in order to compare the expression of the TSC gene products tuberin and hamartin in other human tissues at various prenatal and postnatal ages.…”
Section: Discussionmentioning
confidence: 99%
“…84 These observations may be linked to the putative neuronal migration defect in TSC disease. 85,86 Interestingly, Tsc1 and Tsc2 have recently been shown to regulate axon formation and growth through the key polarity protein SAD kinase, 87 which also regulates cell cycle checkpoints. 88 The question of whether SAD integrates TACC3 with TSC1/TSC2 in neuronal and/or epithelial differentiation, in addition to regulating CHFR function, may appear as a fundamental issue in the study of TSC pathology.…”
Section: Methodsmentioning
confidence: 99%